17AAG Treatment Accelerates Doxorubicin Induced Cellular Senescence: Hsp90 Interferes with Enforced Senescence of Tumor Cells - Upasana Sarangi; Khande Rao Paithankar; Jonnala Ujwal Kumar; Vaidyanathan Subramaniam; Amere Subbarao Sreedhar (AboutScience Srl, 2012)
Hsp90 chaperone has been identified as an attractive pharmacological target to combat cancer. However, some metastatic tumors either fail to respond to Hsp90 inhibition or show recovery necessitating irreversible therapeutic strategies. In response to this enforced senescence has been proposed as an alternate strategy. Here, we demonstrate that inhibiting Hsp90 with 17AAG sensitizes human neuroblastoma to DNA damage response mediated cellular senescence. Among individual and combination drug treatments, 17AAG pre-treatment followed by doxorubicin treatment exhibited senescence-like characteristics such as increased nucleus to cytoplasm ratio, cell cycle arrest, SA- β -gal staining and the perpetual increase in SAHF. Doxorubicin induced senescence signaling was mediated by p53-p21 CIP/WAF-1 and was accelerated in the absence of functional Hsp90. Sustained p16 INK4a and H3K4me3 expressions correlating with unaffected telomerase activation annulled replicative senescence and appraised stress induced senescence. Despite increases in [(ROS)i] and [(Ca 2+ )i], a concomitant increase in cellular antioxidant defense system suggested oxidation independent senescence activation. Sustained activation of survival (Akt) and proliferative (ERK1/2) kinases fosters robustness of cells. Invigorating senescent cells with growth factor or snooping with mTOR or PI3 kinase inhibitors compromised cell survival but not senescence. Intriguingly, senescence-associated secretory factors from the senescence cells manifested established senescence in neuroblastoma, which offers clinical advantage to our approach. Our study discusses tumor selective functions of Hsp90 and discusses irrefutable strategies of Hsp90 inhibition in anticancer treatments.